2013
DOI: 10.17126/joralres.2013.027
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation and validation of Child Oral Impact on Daily Performance index in 11-14-year-old Chilean school children

Abstract: Abstract:The health condition of a population is often rated through clinical indicators. However, the psychological and social impact of diseases on quality of life has been noticed of late. Objective: to adapt, in cultural terms, the Child-Oral Impact on Daily Performance (C-OIDP) questionnaire in its self-administered form and evaluate its psychometric properties among Chilean teenagers aged 11-14 from the city of Licantén, Chile, in 2013. Methodology: A cross-sectional study on scales validation. Face vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
5
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 19 publications
(30 reference statements)
4
5
0
1
Order By: Relevance
“…The most prevalent oral problem reported was sensitive teeth followed by toothache, which were similar to previous studies conducted in Brazil [12], Sudan [16], Italy [15], Israel [19], Malaysia [17], North India [24], and Moroccan [21]. In agreement with most studies [11,12,14,15,17,18,[20][21][22]29], we found that the performances with the highest frequencies impacts were eating, cleaning mouth and smiling; while the performances with the lowest impact were "studying" and relaxing. This is not surprising, because impacts on functional limitations and psychological well being were more prevalant than impact on social wellbeing social during children's transition to adolescence [47,50].…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The most prevalent oral problem reported was sensitive teeth followed by toothache, which were similar to previous studies conducted in Brazil [12], Sudan [16], Italy [15], Israel [19], Malaysia [17], North India [24], and Moroccan [21]. In agreement with most studies [11,12,14,15,17,18,[20][21][22]29], we found that the performances with the highest frequencies impacts were eating, cleaning mouth and smiling; while the performances with the lowest impact were "studying" and relaxing. This is not surprising, because impacts on functional limitations and psychological well being were more prevalant than impact on social wellbeing social during children's transition to adolescence [47,50].…”
Section: Discussionsupporting
confidence: 90%
“…The Turkish C-OIDP showed acceptable internal consistency and test-retest reliability. The Cronbach's alpha was higher than the values reported from previous studies conducted in France [10], England [11], Brazil [12], Peru [13], Spain [14], Italy [15], Chile [18], South India [20] and Moroccan [21]. The ICC was similar to the validation studies in Chile [18], France [10] and South India [20].…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…Bivariate analysis showed that positive rating of oral health was associated with self-perceived satisfaction with appearance of teeth and oral condition, this is in line with previous findings that subjective assessment of oral health correlate strongly with each other as reported by authors of previous studies [21][22][23][24] . However, on multivariate analysis, only the relationship of satisfaction with oral condition was statistically significant.…”
Section: Discussionsupporting
confidence: 91%
“…Solo 2 han sido adaptados transculturalmente y validados en el idioma español: el Early Childhood Oral Health Impact Scale para padres 6,7 y el Child Oral Impacts on Daily Performances Index (Child-OIDP) desarrollado específica-mente para niños 8---10 . Este último recientemente validado en Chile para escolares entre 11-14 años 11 .…”
Section: Introductionunclassified